Phytoplankton Dynamics of Freshwater Lake Varhala in Thane District, Maharashtra (Global Journal of Science Frontier Research, 2017)
Present study deals with the general ecological studies on phytoplankton community in terms of species composition, abundance and distribution in freshwater lake of Thane district. The study done was qualitative and quantitative analysis of phytoplankton. Phytoplankton composition and abundance play an important role in assessing the trophic status of water bodies and helps in optimum utilization of these water resources. Hence, the present work was carried out for a period of one year from February 2015 to January 2016. The samples were collected and identified using standard keys. Altogether 20 genera belonged to three major classes were identified. Among these 10 belonged to Chlorophyceae, 05 to Bacillariophyceae and 05 to Myxophyceae.
Keywords: trophic status; bio-monitoring; water quality; phytoplankton; varhala lake